Anatomical and biochemical changes associated with the development and germination of Araucaria angustifolia seeds - Shibata, Marília; Coelho, Cileide Maria Medeiros; Schmidt, Eder Carlos; Bouzon, Zenilda Laurita; Campos, José Marcello Salabert de; Maraschin, Marcelo (Acta Scientiarum. Biological Sciences, 2019)
This study aimed at assessing the cell cycle, and anatomical and biochemical changes that the embryonic axis of Araucaria angustifolia undergoes during development, focusing on the maturation stage. During all development, cells exhibited intense metabolic activity with an abundance of mitochondria, lipid bodies, and vacuolated cells. The continued accumulation of starch and protein was observed by LM and TEM and indicated by spectra of FTIR. Cell differentiation of the procambium was observed with a thickening of the cell wall and the formation of resiniferous ducts. At Stage III and IV, cells exhibited structural changes such as altered or elongated mitochondria and presence of plastoglobules. These results suggest that there is a gradual transition from developmental metabolism to germination metabolism. Such changes can contribute to the rapid germination of seeds right after their dispersion, making it an ecological strategy to reduce post-dispersal exposure to predators and to avoid damage from reduced moisture.